Sociodemographic profile, work practices, and disease awareness among stone mine workers having silicosis from Central Rajasthan - Dixit, Ramakant; Kuldeep, Rajveer; Goyal, Mukesh; Agarwal, Deepesh; Jalutharia, Jitendra (Lung India, 2023)
ABSTRACT Background and Objectives: Silicosis continues to pose an important health hazard among workers having occupational exposure to stone dust. Several studies have addressed clinical presentation, radiographic and pulmonary function abnormalities in workers with silicosis. This study was planned to analyze sociodemographic profile and awareness about several aspects of silicosis among the stone mine workers visiting our centre. Methods: A questionnaire was administered in a convenient sample of eligible subjects over six years period. The questionnaire was aimed to collect sociodemographic variables, like age, gender, educational status, residential background, smoking status etc., apart from information on work-related profile including protective measures taken. Also knowledge and attitude regarding silicosis was assessed. Silicosis awareness index was also calculated as per the response received. Results: Majority of the study subjects were male (96.6%) with rural background (98.5%). 54.1% subjects were in the age group of 30 to 50 years. 81.9% mine workers were illiterate. The common addictions observed among them included smoking (60%), tobacco chewing (34%), alcohol (20%) etc., Varying duration of work exposure was observed with more than 10 years in 63.4% and more than 20 years in 32.2% workers. The commonest work exposing them to stone dust was breaking stones by chisel and hammer (51%) followed by separation of stone slab (20%) and stone drilling (15%). 80.9% subjects were not aware of the term silicosis, more than 80% were not aware of the symptoms and causes of silicosis. Only one fifth subjects were having awareness of using protection against the disease. Overall awareness about silicosis was better among literate and youngers participants. Conclusions: Stone mining industry reflects male dominance, poor literacy, long working hours for many years, financial compulsion to start and continue the job and very poor awareness regarding the disease silicosis and importance of personal protection at workplace.